All‐dielectric active terahertz photonics driven by bound states in the continuum - Han, Song (2020)
The remarkable emergence of all‐dielectric meta‐photonics governed by the physics of high‐index dielectric materials offers a low‐loss platform for efficient manipulation and subwavelength control of electromagnetic waves from microwaves to visible frequencies. Dielectric metasurfaces can focus electromagnetic waves, generate structured beams and vortices, enhance local fields for advanced sensing, and provide novel functionalities for classical and quantum technologies. Recent advances in meta‐photonics are associated with the exploration of exotic electromagnetic modes called the bound states in the continuum (BICs), which offer a simple interference mechanism to achieve large quality factors (Q) through excitation of supercavity modes in dielectric nanostructures and resonant metasurfaces. Here, a BIC‐driven terahertz metasurface with dynamic control of high‐Q silicon supercavities that are reconfigurable at a nanosecond timescale is experimentally demonstrated. It is revealed that such supercavities enable low‐power, optically induced terahertz switching and modulation of sharp resonances for potential applications in lasing, mode multiplexing, and biosensing.